Tafsir of Harmony:Efforts to Grow Multicultural Awareness - Tri Wahyudi Ramdhan; Saifuddin Saifuddin; Junaidi Junaidi (Al-Thiqah : Jurnal Ilmu Keislaman, 2021)
This study will discuss Qur'anic verses that include messages of "peace" within the context of harmony and tolerance. Examining the sacred text's message of peace is believed to be extremely relevant and vital in the modern era. Human conflicts fueled by religious differences continue to abound across the world. Conflicts do not have to occur between devotees of different religions; they may also arise between factions/groups within the same religion who hold divergent beliefs or interpretations. On that basis, reviving the scriptures' teachings of harmony and peace is critical in order to raise awareness of the value of harmony and tolerance in a society that is prone to division owing to religious differences.